Commercialization of agriculture under population pressure effects on production, consumption, and nutrition in Rwanda - Braun, Joachim von 1950-; Haen, Hartwig de 1941-; Blanken, Jürgen (Internat. Food Policy Research Inst., 1991)
The integration of traditional agriculture into local, national, and international markets is part of a development strategy oriented toward growth. Crop specialization and market integration are seen to hold the promise of wider employment opportunities, larger incomes, and improved consumption and nutrition for the rural poor. Such agricultural development also leads to the emergence of a rural service sector that provides additional employment. But whether the poor obtain a fair share, directly or indirectly, of the gains from commercialization of agriculture is largely determined by the policies and programs adopted. In Commercialization of Agriculture Under Population Pressure: Effects on Production, Consumption, and Nutrition in Rwanda, Research Report 85, Joachim von Braun, Hartwig de Haen, and Juergen Blanken examine the driving forces and the effects of commercialization in a study site in Rwanda, one of the most densely populated areas of Sub-Saharan Africa. This study represents part of IFPRI's continuing research on ensuring food security and alleviating poverty through agricultural commercialization. The present study assesses the interaction of increased commercialization with population growth and the results for production, household real income, family food consumption, expenditures for nonfood goods and services, and the nutritional status of the sample population. It also develops a long-term perspective for agricultural, employment, and nutrition policies.
Keywords: Agriculture; Aliments - Approvisionnement - Politique gouvernementale - Rwanda; Export; Exportations - Rwanda; Nutrition policies; Politique agricole - Rwanda; Politique alimentaire - Rwanda; Productie; Produits agricoles - Commerce - Politique gouvernementale - Rwanda; Rwanda; Voedselvoorziening; Landwirtschaft; Politik; Agriculture and state -- Rwanda; Exports -- Rwanda; Food supply -- Government policy -- Rwanda; Nutrition policy -- Rwanda; Produce trade -- Government policy -- Rwanda; Agrarproduktion; Kommerzialisierung; Bevölkerungswachstum; Rwanda - Population; Rwanda -- Population; Ruanda